2017
DOI: 10.5740/jaoacint.17-0291
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Assessment of 25-Hydroxyvitamin D Reference Material and Proficiency Testing/External Quality Assurance Material Commutability: A Vitamin D Standardization Program Study

Abstract: The Vitamin D Standardization Program (VDSP) coordinated a study in 2012 to assess the commutability of reference materials and proficiency testing/external quality assurance materials for total 25-hydroxyvitamin D [25(OH)D] in human serum, the primary indicator of vitamin D status. A set of 50 single-donor serum samples as well as 17 reference and proficiency testing/external quality assessment materials were analyzed by participating laboratories that used either immunoassay or LC-MS methods for total 25(OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…2019;143:1531-1538; doi: 10.5858/arpa.2018-0625-CP) V itamin D measurement techniques and proper utilization have been a source of interesting debate in the laboratory medicine community for quite some time. [1][2][3][4][5][6][7][8][9][10] Vitamin D is made up of several fat-soluble secosteroids. 11,12 The 2 major forms of vitamin D are vitamin D 2 or ergocalciferol, which is derived from plants, and vitamin D 3 or cholecalciferol, which is derived from animal sources.…”
mentioning
confidence: 99%
“…2019;143:1531-1538; doi: 10.5858/arpa.2018-0625-CP) V itamin D measurement techniques and proper utilization have been a source of interesting debate in the laboratory medicine community for quite some time. [1][2][3][4][5][6][7][8][9][10] Vitamin D is made up of several fat-soluble secosteroids. 11,12 The 2 major forms of vitamin D are vitamin D 2 or ergocalciferol, which is derived from plants, and vitamin D 3 or cholecalciferol, which is derived from animal sources.…”
mentioning
confidence: 99%
“…Plasma samples collected during the first and third trimester visits and at delivery ( 17 ) were used to measure 25OHD and categorize participants as having concentrations <30, <40, <50, and 50–125 nmol/L; we also categorized plasma 25OHD >125 nmol/L to explore concentrations at which there may be concern for adverse effects ( 1 ). Two methods were used to measure maternal plasma 25OHD, and results were standardized according to standard reference materials ( 12 , 13 ). Initially, plasma 25OHD (first trimester: n = 1188; third trimester: n = 762; and delivery: n = 656) was measured using Total 25-hydroxyvitamin D immunoassay kits and the LIAISON autoanalyzer platform (Diasorin Inc.), as previously described ( 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, no pregnancy study in Canada has reported on the recommended population cut point of serum 25OHD ≥40 nmol/L ( 1 ). In addition, the majority of reports predate the launch of the Vitamin D Standardization Certification Program (VDSCP) ( 12 , 13 ). The VDSCP aims to improve the accuracy and comparability of 25OHD measurements across assays and laboratories around the world.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 represent an aspirational goal for fully harmonized and/or standardized methods, although relatively few methods in clinical chemistry have completed this rigorous process to date, and to our knowledge no routine MS-based methods are among these fully harmonized or standardized methods, although in the small-molecule realm, significant progress toward that goal has been made by laboratories that have voluntarily participated in the Centers for disease Control and Prevention’s (CDC’s) Hormone Standardization (HoSt) Program 3 and Vitamin D Standardization-Certification Program (VDSCP). 4…”
Section: Approaches To Harmonization and Standardizationmentioning
confidence: 99%
“…Included among the harmonization success stories to date are efforts such as the CDC’s HoSt program, which is focused on serum hormones like thyroid-stimulating hormone, 21 estradiol and, testosterone, 22 and the NIH/Office of Dietary Supplements Vitamin D Standardization Program. 4,23 Other organizations have also led efforts to create international standards for measurands like serum immunoglobulin E 24 (College of American Pathologists (CAP), WHO), free thyroxine, 25 triiodothyronine 26 (IFCC), and for lipid function tests such as cholesterol 27 (NIST), and kidney function measurement of serum creatinine 28 (NIST). In some cases, atypically, harmonization of clinical assays results from only a single manufacturer producing a test specific for a given measurand (N terminal-proBNP, cardiac troponin T) 5,29 (Roche Diagnostics, Risch-Rotkreuz, Switzerland).…”
Section: Literature Review/bibliographymentioning
confidence: 99%